The association between season and meteorological factors on clinical outcomes after fresh embryo transfer: a cohort study from Central Plains, China - Li, Hao; Li, Xin; Li, JinYu; Ma, YuMeng; Li, Gang (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate whether seasonal variations and meteorological factors influence pregnancy outcomes in women undergoing in vitro fertilization/Intracytoplasmic sperm injection and embryo transfer(IVF/ICSI-ET) treatment.Materials and methodsWe conducted a retrospective cohort study of women who underwent IVF/ICIS-ET for the first time at the Reproductive Medicine Center of the First Affiliated Hospital of Zhengzhou University from January 1, 2011, to December 1, 2021. A total of 24420 cycles were collected. They were divided into four groups according to the oocyte retrieval date. The main outcome measures were clinical pregnancy rate and live birth rate. Binary logistic regression was used to explore the factors affecting clinical pregnancy rate and live birth rate.ResultsIn this study, the live birth rate of cycles with oocyte retrieval performed in summer was significantly higher than those in spring, autumn, and winter (61.24% [4859/7934] vs. 59.09% [3074/5202] vs. 58.89% [3676/6242] vs. 57.70% [2909/5042]; P<0.001), with the summer group also exhibiting the lowest abortion rate among the four seasons. Notably, despite these differences, no statistically significant variations were observed in biochemical pregnancy rates or clinical pregnancy rates across the groups (P>0.05). Taking spring as the reference, the live birth rate in summer was higher (aOR=1.079,95% CI: 1.004-1.160), and the abortion rate was lower (aOR = 0.841,95% CI: 0.746-0.948). The live birth rate and abortion rate in autumn and winter were not significantly different from spring. Multivariate logistic regression analysis showed higher daily average temperature, and humidity at the time of oocyte retrieval increased the live birth rate (OR = 1.005, 95% CI = 1.002–1.007; OR = 1.004, 95% CI = 1.001–1.006).ConclusionsIn women who undergo IVF/ICSI treatment, the season ambient temperature, and humidity on the date of the oocyte retrieval may impact embryo development and live birth.